A case of encephalomalacia in pigeon - Gül, Y; Dabak, M; Issi, M (Scientific Technical Research Council Turkey, 2001)
In this report, a case of encephalomalacia in a pigeon brought into the Clinic of internal Medicine (Firat University, Faculty of Veterinary Medicine - Elazig - TURKEY) for examination and treatment is presented.
Bir Güvercinde Ensefalomalasi Olgusu
Keywords: pigeon; encephalomalacia; vitamin E